2019
DOI: 10.1002/jcb.28394
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DINO (damage induced noncoding) represses the development of gastric cancer by modulating p21 and Bcl‐2 Associated X Protein (Bax) expression

Abstract: lncRNAs are responsible for a variety of diseases, including gastric cancer (GC). Many recent studies have reported that lncRNAs can serve as crucial regulators of various genes. Nevertheless, the biological function of lncRNA damage induced noncoding (DINO) remained poorly investigated in GC. Therefore, in our present study, the detailed role of DINO was investigated. It was manifested that DINO was significantly downregulated in GC tissues. Then, DINO was modulated by infecting LV-DINO or by LV-shRNA in BGC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…While p53 -null mice predominantly develop spontaneous T lymphomas of thymic origin, we were surprised to observe no incidence of T cell lymphoma in Dino −/− mice ( Table 1 ) [ 18 , 26 ]. Given the well-established role of Dino in p53 pathway regulation in multiple cell types, including T cells [ 16 , 17 , 27 ], the absence of spontaneous T cell lymphoma in Dino -null mice is particularly striking. p53 is critical for the protection of cells against radiation-induced carcinogenesis [ 28 ], particularly in the thymus, which undergoes extensive p53-dependent apoptosis after radiation [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…While p53 -null mice predominantly develop spontaneous T lymphomas of thymic origin, we were surprised to observe no incidence of T cell lymphoma in Dino −/− mice ( Table 1 ) [ 18 , 26 ]. Given the well-established role of Dino in p53 pathway regulation in multiple cell types, including T cells [ 16 , 17 , 27 ], the absence of spontaneous T cell lymphoma in Dino -null mice is particularly striking. p53 is critical for the protection of cells against radiation-induced carcinogenesis [ 28 ], particularly in the thymus, which undergoes extensive p53-dependent apoptosis after radiation [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in cervical cancer cells, it has been shown that DINO activation occurs through a pathway that is independent of ATM/CHK2 ( Sharma and Munger 2020a ). Recent studies show that DINO is silenced in human cancers ( Liu et al, 2019 ; Marney et al, 2021 ), and some evidence shows that a region of the DINO/CDKN1A locus is hypermethylated, leading to the silencing of DINO but not CDKN1A ( Marney et al, 2021 ). Furthermore, silencing DINO in a model of primary HFKs E7+ HPV16+ using shRNAs decreases sensitivity to doxorubicin ( Sharma and Munger 2020b ).…”
Section: The Pathogenetic Role Of Ncrnas In Hpv+ Cancersmentioning
confidence: 99%
“…Using the TCGA Pan-Cancer database, it was found that many tumors have methylation in the CpG shore downstream of the DINO TSS associated with lower expression, which would explain the low mutation rate in this gene ( Marney et al, 2021 ). In tumors of patients with gastric cancer, DINO is downregulated compared to adjacent tissue ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%